Electrical Tomography Sensor Modelling for Detection of Fuel Proportion in Vessel - Rian Fahrizal; Jaga Sobar Julianto; Alief Maulana; Rocky Alfanz; Ceri Ahendyarti; Rohmadi Rohmadi; Imamul Muttakin (Universitas Ahmad Dahlan, 2023)
Electrical capacitance volume tomography (ECVT) is a method for determining the volumetric distribution of dielectric permittivity using the capacitance measurement principle. The determination of volumetric distribution of dielectric permittivity is important to regulate a process in which quantity of materials is a decisive parameter such as in industrial setting or vehicle sub-system. ECVT is a relatively fast and non-radiating method to observe spatio-temporal phenomena inside a process, making it a valuable technique. Sensor modelling and image reconstruction study are essentials in designing a suitable imaging system based on measurements from plurality of electrodes providing higher degree of information being observed. This research conducts sensor modelling with varying fuel objects in the interior of a cylindrical vessel. The capacitance value was simulated between a combination of eight electrodes mounted encapsulating the tube. Each measured electrode was given an excitation voltage as a source of an electrostatic field, which interacts with the object’s presence. The objects in this study are benzene, kerosene, and diesel fuel, along with reference dielectric values of water and air. Image reconstruction used the linear back projection (LBP) method. Matrix operations between sensor’s pre-defined sensitivity and capacitance values produce data that can be plotted into an image estimating the true distribution of objects. Capacitance values from modelling are proportional to the actual object’s permittivity. The reconstruction provides qualitative information on the proportion of fuel in the vessel based on the capacitance value. Images have distinct values according to the presence of different objects under investigation. The research contribution is a proof of concept in using capacitance tomography to detect different fuels inside an enclosed tank at modelling stage. In addition, this study serves as a guideline for implementing a non-invasive and non-intrusive system for determining proportions of materials of interests inside a certain setup.